Performance of promising sweet potato genotype NSP-7 in South Gujarat - Himani B. Patel; C. G. Intwala; Kiran P. Suthar; Nilima Karmakar; G. B. Desai (JOURNAL OF ROOT CROPS, 2024)
Sweet potato has a great potential for productivity and energy output. The demand for sweet potato is increasing due to nutritional concerns leading to the availability of diverse genotypes for tuber colour, taste, quality parameters etc. In present study, one promising genotype NSP-7, was identified with higher tuber yield (23.39 t ha-1), resistance to sweet potato weevil and slight pink skin colour having pale yellow flesh suitable for cultivation in south Gujarat, India. The morphological, biochemical and molecular analysis revealed NSP-7 as distinct genotypes. It has a high amount of starch (17.28%), fibre (3.97%) and protein (1.68%) as well as good cooking quality as compared to checks. Based on quality parameters and yield performance over the years and location, the NSP-7 genotype is recommended for cultivation in the south Gujarat region for maximum economic benefits. Keywords : Sweet potato, NSP-7, Sweet potato weevil, Yield, Organoleptic score